2016
DOI: 10.1017/s0305000915000549
|View full text |Cite
|
Sign up to set email alerts
|

Older age of onset in child L2 acquisition can be facilitative: evidence from the acquisition of English passives by Spanish natives

Abstract: A project of this nature and size involves the cooperation of many people to whom we are indebted and owe much gratitude. We wish to thank all the children and their parents for their enthusiasm and participation over the years; it was a pleasure to see your development and growth-much more than just in your language. To the teachers and especially the administration at the Colegio Berchmans, we cannot thank you enough. Finally and most notably, a very large thank you to Eliana Herrera Laguna, the director of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The limited impact could be due to many children having limited or no schooling in Arabic. It is relevant to ask why older age was not associated with stronger L2 outcomes, in contrast to previous research (Chondrogianni & Marinis, 2011;Golberg et al, 2008;Paradis, 2011;Rothman et al, 2016). Perhaps the cognitive capacity variance due to older age was specified mainly by MAT; there was a moderate correlation between MAT and age (Table 3).…”
Section: Cognitive Age and School Factorsmentioning
confidence: 78%
See 1 more Smart Citation
“…The limited impact could be due to many children having limited or no schooling in Arabic. It is relevant to ask why older age was not associated with stronger L2 outcomes, in contrast to previous research (Chondrogianni & Marinis, 2011;Golberg et al, 2008;Paradis, 2011;Rothman et al, 2016). Perhaps the cognitive capacity variance due to older age was specified mainly by MAT; there was a moderate correlation between MAT and age (Table 3).…”
Section: Cognitive Age and School Factorsmentioning
confidence: 78%
“…Age, Cognitive Factors, and Bilingual Development Not only language environment factors, but also child-internal factors, such as age of L2 acquisition onset (AOA) and cognitive capacities, influence bilingual development. Studies that have controlled for the amount of L2 input have shown that older AOA within the early childhood years is associated with more advanced L2 development in vocabulary and morphosyntax for children in L2-majority contexts (Chondrogianni & Marinis, 2011;Golberg et al, 2008;Paradis, 2011), as well as for children in instructed L2 contexts (Rothman et al, 2016). These researchers hypothesized that the older-learner advantage is likely due to beginning L2 acquisition with greater linguistic and cognitive maturity.…”
Section: Maternal Educationmentioning
confidence: 99%
“…Evidence for parallels between child L2 and adult L2 has been reported for passive in German (Wegener, 1998) and for verb-second and subject-verb agreement in German (Haberzettl, 2005; Rothweiler, 2006; Chilla, 2008). However, in a study on passives in English, Rothman et al (2016) found that child L2 learners outperformed children with an age of onset of 4 to 5 years which they attributed to so-called conceptual transfer from the L1 to the learners’ L2. Many studies on eL2 acquisition (age of onset of 3 to 4 years) have found parallels between eL2 and monolingual children.…”
Section: Factors Influencing Child Bilingual Acquisitionmentioning
confidence: 98%
“…Clearly, cognitive and linguistic factors will interact at schoolage, where working memory and other cognitive functions have developed, whereas specific discovery mechanisms may no longer be easily available (Meisel, 2009), and language is not only learned by naturalistic exposure but also crucially in a classroom environment. It has been shown that the acquisition of the lexicon (Goldberg, Paradis, & Crago, 2008) and of complex constructions, such as passive (Rothman et al, 2016), proceeds faster in older than in younger children due to their greater cognitive resources. Because of the greater variation described for adult L2 development (see Birdsong, 2018, for an overview) and also for late child L2, other factors such as length of exposure (LoE) or working memory capacities have been explored (Farnia & Geva, 2011;Paradis, 2011).…”
Section: Late Child L2 Acquisition By Newcomers and Refugee Childrenmentioning
confidence: 99%